Edukasi Pengawasan, Kepemimpinan dan Kompensasi terhadap Disiplin Kerja Karyawan Pada Masyarakat di Kecamatan Medan Denai - Juniarti; Putri Pradini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The purpose of this community service is to increase understanding of supervision, leadership and compensation on employee work discipline in the community in Medan Denai sub-district. The specific target in this community service is that the people of Medan Denai sub-district know what supervision, leadership and compensation are that affect work discipline. The materials presented in this community service are: what is supervision, leadership, and compensation. The relationship will affect employee work discipline in Medan Denai sub-district so that the community gets a solution in improving supervision, leadership, and compensation. From this community service, the results show that the Medan Denai sub-district community has known and understood the importance of supervision, leadership, and compensation to employees so that the community is able to improve work discipline and better work performance.